Hardness testing methods: Brinell, Rockwell, Vickers. Book 2. Macro, Micro, and Nano Range. Laboratory assignments 13–20 : methodological instructions - Moshchenok, Vasyl (Independently published, 2025)
The book Hardness Testing Methods: Brinell, Rockwell, Vickers. Book 2. Macro, Micro and Nano Range is intended for students of technical universities and colleges as a practical guide to mastering modern methods of hardness determination across macro-, micro-, and nanoscale levels. It presents detailed methodologies for measuring volume, surface, projection, kinetic, and nanohardness using various indenters, including spherical, Vickers, and Berkovich geometries. Emphasis is placed on the practical application of international standards and advanced instrumentation, providing learners with the foundational knowledge and experimental skills needed for accurate and comprehensive hardness evaluation of engineering materials.
Keywords: hardness testing; brinell method; rockwell method; vickers method; macrohardness; microhardness; nanohardness; materials science; berkovich indenter; kinetic hardness; surface hardness; projection hardness; volume hardness; engineering materials; technical education; practical guide; international standards